Mappadendang: Values of Togetherness in the Bugis Tribe and Their Implications in Social Studies Learning - Moh. Zulkarnaen; Sudrajat Sudrajat; Hasmiah Herawaty; Sandesh Bandhu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines how togetherness values embedded in the mappadendang tradition can be pedagogically operationalized in Social Studies (IPS) learning at the madrasah level. While previous studies have extensively documented mappadendang as a Bugis harvest ritual rich in social values, little attention has been given to its systematic integration into formal IPS pedagogy, particularly within Islamic junior secondary education. Addressing this gap, the study adopts a qualitative, focused ethnographic design centered on educational practice rather than cultural ritual alone. Data were collected through in-depth interviews, participatory observations, and document analysis involving IPS teachers, students, school leaders, and local cultural actors at MTs DDI Amparita, South Sulawesi. The findings reveal that togetherness in mappadendang is manifested through collective responsibility, intergenerational participation, and community-based cooperation, which function as lived social experiences closely aligned with core IPS competencies. Rather than merely listing cultural values, this study demonstrates how these practices can be translated into contextual learning resources that support collaborative and socially grounded IPS instruction. The study contributes conceptually to ethnopedagogy by positioning local tradition as a primary source of social knowledge, and pedagogically by offering a culturally grounded framework for learning IPS based on local wisdom in madrasah contexts.